Molecular and pathological identification of maize genotypes having Wsm gene governing resistance against MDMV and MCDV (Journal of the Bangladesh Agricultural University, 2018)
Maize is seriously affected by different viruses like Maize Dwarf Mosaic Virus (MDMV) and Maize Chlorotic Dwarf Virus (MCDV) throughout the world. In Bangladesh, no genotype has been identified yet as a source of resistant gene against MDMV and MCDV. The study was carried out with the objective to screen nine maize genotypes carrying Wsm gene using three sets of Single Sequence Repeat (SSR) marker. Maize plants were inoculated with viruses. Symptoms were scored at 7, 10 and 14 dpi (days post inoculation) to calculate infection percentage and Area Under Disease Progress Curve (AUDPC). The molecular result indicated that BHM-7, BHM-5, V-92, Uttaran and Duranta carried Wsm gene, but according to pathological test, functional resistance was observed for only BHM-7, V-92 and Uttaran on the basis of infection percentage and AUDPC score. BHM-7 (BARI Hybrid Maize 7) was noticed as the best one for showing resistance against MDMV and carrying Wsm gene. No genotype was found to govern resistance against MCDV.J. Bangladesh Agril. Univ. 16(2): 208-214, August 2018